Differentiating malignant from benign gastric mucosal lesions with quantitative analysis in dual energy spectral computed tomography: Initial experience. Issue 2 (January 2017) - Meng, Xiaoyan; Ni, Cheng; Shen, Yaqi; Hu, Xuemei; Chen, Xiao; Li, Zhen; Hu, Daoyu
Abstract : Abstract: To investigate the value of quantitative analysis in dual energy spectral computed tomography (DESCT) for differentiating malignant gastric mucosal lesions from benign gastric mucosal lesions (including gastric inflammation [GI] and normal gastric mucosa [NGM]). This study was approved by the ethics committee, and all patients provided written informed consent. A total of 161 consecutive patients (63 with gastric cancer [GC], 48 with GI, and 50 with NGM) who underwent dual-phase contrast enhanced DESCT scans in the arterial phase (AP) and portal venous phase (PVP) were included in this study. Iodine concentration (IC) in lesions was derived from the iodine-based material-decomposition images and normalized to that in the aorta to obtain normalized IC (nIC). The ratios of IC and nIC between the AP and PVP were calculated. Diagnostic confidence for GC and GI was evaluated with reviewing the features including gastric wall thickness, focal, and eccentric on the conventional polychromatic images. All statistical analyses were performed by using statistical software SPSS 17.0 (SPSS, Chicago, IL). IC and nIC in GC differed significantly from those in GI and NGM, except for nICAP in comparing GC with GI. Mean nIC values of GC (0.18 ± 0.06 in AP and 0.62 ± 0.16 in PVP) were significantly higher than that of NGM (0.12 ± 0.03 in AP and 0.37 ± 0.08 in PVP) (all P < 0.05). There was also significant difference for IC values in GC, GI, and NGM (24.19 ± 8.27, 19.07 ± 5.82, and 13.61 ± 2.52 mg/mL, respectively, in AP and 28.00 ± 7.01, 24.66 ± 6.55, and 16.94 ± 3.06 mg/mL, respectively, in PVP). Based on Receiver Operating Characteristic Curve analysis, nIC and IC in PVP had high sensitivities of 88.89% and 90.48%, respectively, in differentiating GC from NGM, while the sensitivities were 71.43% and 88.89% during AP. Ratios IC and nIC ratios did not provide adequate diagnostic accuracy with their area under curves less than 0.65. With the conventional features, the diagnostic accuracies for GC and GI were 75.0% and 98.0%, respectively. Quantitative analysis of DESCT imaging parameters for gastric mucosa, such as nIC and IC, is useful for differentiating malignant from benign gastric mucosal lesions.